Alveolar and exhaled NO in relation to asthma characteristics – effects of correction for axial diffusion. Issue 8 (4th June 2014) - Heijkenskjöld‐Rentzhog, C.; Nordvall, L.; Janson, C.; Borres, M. P.; Alving, K.; Malinovschi, A.
Abstract Background Inflammation in the small airways might contribute to incomplete asthma disease control despite intensive treatment in some subgroups of patients. Exhaled NO (FeNO) is a marker of inflammation in asthma and the estimated NO contribution from small airways (CalvNO) is believed to reflect distal inflammation. Recent studies recommend adjustments of CalvNO for trumpet model and axial diffusion (TMAD‐adj). This study aimed to investigate the clinical correlates of CalvNO, both TMAD‐adjusted and unadjusted. Methods Asthma symptoms, asthma control, lung function, bronchial responsiveness, blood eosinophils, atopy and treatment level were assessed in 410 subjects, aged 10–35 years. Exhaled NO was measured at different flow‐rates and CalvNO calculated, with TMAD‐adjustment according to Condorelli. Results Trumpet model and axial diffusion‐adjusted CalvNO was not related to daytime wheeze (P = 0.27), FEF50 (P = 0.23) or bronchial responsiveness (P = 0.52). On the other hand, unadjusted CalvNO was increased in subjects with daytime wheeze (P < 0.001), decreased FEF50 (P = 0.02) and with moderate‐to‐severe compared to normal bronchial responsiveness (P < 0.001). All these characteristics correlated with increased FeNO (all P < 0.05). Unadjusted CalvNO was positively related to bronchial NO flux (J'awNO) (r = 0.22, P < 0.001) while TMAD‐adjCalvNO was negatively related to J'awNO (r = −0.38, P < 0.001). Conclusions Adjusted CalvNO was not associated with any asthma characteristics studied in this large asthma cohort. However, both FeNO and unadjusted CalvNO related to asthma symptoms, lung function and bronchial responsiveness. We suggest a potential overadjustment by current TMAD‐corrections, validated in healthy or unobstructed asthmatics. Further studies assessing axial diffusion in asthmatics with different degrees of airway obstruction and the validity of proposed TMAD‐corrections are warranted.